Robot Pintar Line Tracer Pengantar Makanan dan Minuman Restoran Berbasis Mikrokontroller Atmega 8535 - Muhamad Rifzki Akbar; Hermansyah Alam; Dicky Lesmana3 (Jurnal Serambi Engineering, 2024)
This ATMega 8535 microcontroller-based restaurant food and beverage delivery line tracer smart robot is designed to facilitate the work of restaurant owners and attract visitors. This food and beverage delivery line tracer smart robot is responsible for delivering food and beverages from the chef's place to the ordering customer's table. This robot has four main circuits, including the ATMega 8535 microcontroller circuit as the main controller of the line tracer robot, the H-bridge driver circuit as the controller of the DC motor that pushes the food pot rack and changes the direction of rotation of the motor that pushes the food pot, the sensor driver circuit to read the path of the track so that the robot stays on the track, and the L293D motor driver circuit to control the speed of the DC motor, the direction of rotation of the DC motor, and the voltage amplifier of the DC motor that drives the robot body. This robot uses four photodiode sensors to read the robot's trajectory line. The results obtained from testing the line tracer robot system are that when the table selection button is pressed, the robot moves periodically from the home base to the customer's table to automatically deliver food by following the black line trajectory.